Health impact assessment to predict the impact of tobacco price increases on COPD burden in Italy, England and Sweden - Elaine Fuertes (Nature Portfolio, 2021)
Abstract Raising tobacco prices effectively reduces smoking, the main risk factor for chronic obstructive pulmonary disease (COPD). Using the Health Impact Assessment tool “DYNAMO-HIA”, this study quantified the reduction in COPD burden that would occur in Italy, England and Sweden over 40 years if tobacco prices were increased by 5%, 10% and 20% over current local prices, with larger increases considered in secondary analyses. A dynamic Markov-based multi-state simulation modelling approach estimated the effect of changes in smoking prevalence states and probabilities of transitioning between smoking states on future smoking prevalence, COPD burden and life expectancy in each country. Data inputs included demographics, smoking prevalences and behaviour and COPD burden from national data resources, large observational cohorts and datasets within DYNAMO-HIA. In the 20% price increase scenario, the cumulative number of COPD incident cases saved over 40 years was 479,059 and 479,302 in Italy and England (populous countries with higher smoking prevalences) and 83,694 in Sweden (smaller country with lower smoking prevalence). Gains in overall life expectancy ranged from 0.25 to 0.45 years for a 20 year-old. Increasing tobacco prices would reduce COPD burden and increase life expectancy through smoking behavior changes, with modest but important public health benefits observed in all three countries.